PENGARUH PENAMBAHAN LOGAM TRANSISI NIKEL TERHADAP SIFAT FISIS NANOROD ZnO - Sumarti Sumarti; Iwantono Iwantono; Awitdrus Awitdrus (Komunikasi Fisika Indonesia, 2020)
Nickel-doped ZnO nanostructures have been successfully grown using seed mediated hydrothermal method. The growth of ZnO nanostructures has been done by concentration of the Ni-doped solution, is 8 mM with the growth temperature of  90°C in 7 hours. The grown ZnO nanostructures were characterized by using UV-Vis Spectroscopy, FESEM, and XRD. The UV-Vis spectra of the samples showed that the ZnO nanorod is hexagonal in shape with a strong absorption occured in the wavelength range of 300-380 nm. The FESEM images showed that geometrical shape of Ni-doped ZnO nanostructures are nanorod with a hexagonal and nanoflower faced shapes. XRD patterns observed show five diffraction peaks at 2θ: 32,09°; 34,76°; 36,65°; 47,95° and 56,97° for Ni doped ZnO nanostructures with crystal orientation of (100), (002), (101), (102) and (110) respectively. The strongest line was found in the crystal plane of (101).